Youth-Led Catfish Farming for Village Empowerment: Budidaya Ikan Lele yang Dipimpin oleh Pemuda untuk Pemberdayaan Desa - Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2025)
General background: Rural communities face uneven development and limited livelihood opportunities, increasing the need for local empowerment initiatives. Specific background: In Banjarkemantren Village, Karang Taruna (youth organization) initiated catfish (lele) cultivation using biofloc systems to strengthen food security and incomes. Knowledge gap: Despite activities and infrastructure, harvests have not consistently reached targets and barriers in marketing, technical skill, and facilitation remain. Aims: This study describes and analyzes Karang Taruna’s role (motivator, facilitator, mobilizer) in empowering the community through catfish farming. Results: Qualitative findings (observations, interviews, documentation) indicate strong motivator activity, ongoing innovations as mobilizer, but limited facilitation in marketing networks and technical dissemination—yielding increasing but subtarget harvests across three cycles. Novelty: The paper documents a youth-driven, biofloc-based empowerment model in a village context and empirically maps its three-role performance to observed production gaps. Implications: Strengthening technical capacity, formal market linkages, and active facilitation by Karang Taruna can improve yields and scale local livelihood outcomes.